The quality of the public service of transportation of urban bus in the city of Tulcán and its incidence in the satisfaction of the users - Paredes Terán, Jennifer Carolina; Pozo Champutíz, Sandra Elizabeth; Villarreal Cupacán, Beatriz Mireya (SATHIRI, 2019)
In this research, attributes, and factors such as accessibility, security, image, comfort, cleanliness, routes, frequencies, user attention that emerge through a deployment of variables focused on the quality of service and satisfaction of the users were identified. users inserted under an organizational and managerial approach that allowed to determine and understand the diverse needs of the users and deficiencies that can present the operators, the units, competent authorities that assume the subject of transport and mobility and thus be able to provide a public service of urban transport Attached to the new social, technological, legal and inclusive demands in face of the demands of urban modernity. Under this perspective in the research, an information collection instrument was applied to a sample of 205 resulting from a population of 53,558 inhabitants of the urban area of the city of Tulcán, which allowed a measurement of the aforementioned attributes and evaluation the perception of the quality of service of public bus transportation in the city of Tulcán.